Conscience on stage : the Comedia as casuistry in early modern Spain - Kallendorf, Hilaire, 1974- (University of Toronto romance series (Unnumbered), 2007)
It is no accident that some variation of the question 'What should I do?' appears in over three-quarters of the comedic plays of the Spanish Golden Age. Casuistical dialogue was a concern, even an obsession, of Spanish playwrights during the seventeenth century, many of whom were educated by Jesuit casuists. Conscience on Stage is a study of casuistry or case morality as the foundation for a poetics of seventeenth-century Spanish comedias.Hilaire Kallendorf examines the Jesuit upbringing and casuistical education of major playwrights of the Spanish Golden Age, many of whom were also priests, and introduces the vocabulary of casuistry, as expressed in both confessors' manuals and in stage plays. Engaging issues of class, gender, and age to explore scenes of advice-giving and receiving, she demonstrates how the culture-specific construct of 'conscience' in early modern Spain can be recovered by means of a Foucauldian genealogy, which enlists the skills of philology at the service of a larger vision of the history of ideas. This study outlines and reiterates the relationship of theatre to casuistry, the Jesuit contributions to Spanish literary theory and practice, and the importance of casuistry for the study of early modern subjectivity.